Порівняльне дослідження японської культури - Окунісі Сюнсуке (Народна творчість та етнографія, 2009)
The origin of multinational population of Japan is explored in the article. This problem is examined first of all as linguistic, although the row of hypotheses about the (relation of the Japanese myths and rituals with Ancient Roman, Austrian myths and with the myths of other people of the world are pointed.